Exploring the Personal Mastery of Educational Leaders: FieldTransFormation[superscript 360] and Its Validation in the Austrian Leadership Academy - Gregorzewski, Malte; Schratz, Michael; Wiesner, Christian (Center for Educational Policy Studies Journal, 2018)
This paper introduces the innovative model FieldTransFormation[superscript 360] and its aim to help educational leaders in assessing their personal mastery. Moreover, it presents empirical findings from its first exploratory application in an Austrian leadership framework. In a first conceptual part, the theoretical underpinnings and the context of the origin of the model are outlined with reference to similar approaches in the area of school leadership. In the following part, the application of the model is introduced through the explanation of the methodology and how the model is turned into a self-assessment instrument. Insights into the results of its exploratory application in the Austrian Leadership Academy are presented in the empirical part. Its first application serves as the consolidation and validation of FieldTransFormation[superscript 360] as a meaningful self-assessment tool for the professional development of school leaders. The results of the exploratory approach with participants in the Austrian Leadership Academy suggest that the model and its instrument can be regarded as a robust assessment tool for the development of a deeper understanding about the transformative power through personal and professional development in the lived experience of educational leadership.
Keywords: Faculty Development; Foreign Countries; Instructional Leadership; Leaders; Models; Transformational Leadership